Study of Adsorption Kinetics of Fe Metal in Batik Cual Waste using Chitosan of Rice Crab Shells - Fadillah Ramadhani; Widodo Budi Kurniawan; Aldila, Herman (TIME in Physics, 2023)
Chitosan from freshwater crab (Parathelphusa convexa) shell has been successfully extracted and its kinetic adsorption models for iron (Fe) metal ions in the batik cual waste solution (BCWs) were studied. Freshwater crab chitosan (FwC-Chi) was extracted via demineralization, deproteinization, decolorization, and deacetylation steps. The deacetylation degree value of FwC-Chi was 97.92% determined through FTIR spectra using the baseline method. In this study, iron metal ions distributed in the BCWs homogeneously with the concentration of iron (Fe) was 0.43 mg/L determined by atomic absorption spectroscopy (AAS). The performance of FwC-Chi adsorption on iron in the BCWs with the ratio of 1:100 (w/v) for various contact times of 30, 60, 90, 120, 150, 180, 210, and 240 minutes respectively while stirring homogeneously at room temperature. The result showed that the adsorption kinetic models for iron metal ion in the BCWs follows Behnajady-Modirshahla-Ghanbery (BMG) and pseudo-second-order kinetic model. Based on this model we found that the decrease of iron concentration is indicated by the decolorization of the waste color. It’s clear that there is a relationship between the waste color with the concentration of iron metal in the BCWs. The coefficient of decolorization decay, rate of decolorization and adsorption rate coefficient was 1,366 g-1, 16,053 g min-1, and 0,043 g mg-1 min-1 respectively achieved based on this model.